On farm pre-weaning performance and variable cost of rearing of Sunandini replacement dairy calves in humid tropics of Kerala - Thomas, Marykutty (Indian Journal of Dairy Science, 2016)
A retrospective study was undertaken to analyse the pre weaning performance inclusive of growth, mortality and disease incidence, and variable cost of raising Sunandini replacement dairy calves in humid tropics. The mean birth weight, weaning body weight (90 days of age) and average daily gain were 22.9kg, 40kg and 0.191kg respectively. Sunadini calves showed better pre weaning survivability of 95.46%. The total variable cost of rearing a pre weaning calf was `8395.7256 equivalent of `93.29/calf/day. The feed, labour and veterinary aid components constituted 84%, 14% and 2% of total variable cost. Milk fed to calves constituted the major share of 85.43% of feed cost. The significant high correlations between body weight traits and variable cost is useful in developing prediction equations. The exorbitant variable cost of raising a calf up to weaning demands for the formulation of an early weaning recipe suitable to the humid tropics of Kerala.